PENINGKATAN AKSES KUALITAS PELAYANAN KESEHATAN ANAK DI KOTA MEDAN: PERAN DOKTER KELUARGA - BUTARBUTAR, HARRY (LP2MTBM MAKARIOZ, 2022)
The aim of this research is to determine the influence of increasing access to health for children on increasing the role of family doctors in improving counseling so that children can improve their growth and development. The existing research method is to use a quantitative descriptive approach using analytical methods. From the results of existing research, it can be explained that the average age of children in the Medan city area whose health is disturbed is in the age range of 11-14 years and who do not have access to adequate health services. The results of the research also state that improving poor access to health which is related to the lack of knowledge and skills of family doctors will worsen children's health conditions, and the lack of the role of doctors, especially the lack of counseling, will actually make children's health conditions worse. The conclusion are increasing access to health services and increasing counseling can speed up children's recovery in a comprehensive manner, where access to health services and counseling provided by family doctors will increase children's enthusiasm to recover and be healthy again, so that they will easily increase their immune system and avoid existing diseases.